Assessing the role of small farms in regional food systems in Europe: Evidence from a comparative study - Rivera, Maria (2020)
The importance of small farms is well established and recognized in developing countries, but far less is known about their role in Europe, where agriculture is largely industrialized. In this paper we use a comparative analysis of evidence from 15 European countries to assess the contribution of small farms to regional food production and availability, across geographies and products. We collected information about regional (NUTS-3) level production, trade and consumption of 91 products across 25 European regions using official statistics, expert interviews, and farm-level surveys. This information was used to develop product-specific systems maps which were coded and systematised. We then used a Random Forest algorithm to establish which system variables were more likely to explain variation along two dimensions: the contribution of small farms to regional production (i.e. proportion of regional production coming from small farms) and their contribution to regional food availability (i.e. proportion of their production that is consumed within the region). Our results suggest that the contribution of small farms to regional production is closely related to the relative abundance of small farms in the agricultural landscape, while their contribution to regional food availability is driven by structure of specific supply chains and the market linkages available to small farms, and in particular the degree of selfprovisioning and direct sales to consumers. These findings shed light on the relatively unknown word of European small farms, showing their importance in food production and availability, and providing new evidence to inform more effective policy for these often-neglected actors of the food system.